Solar-driven Redox Hydrogen Production - Deng Yimin; Liu Helei; Luo Hui; Bai Liju; Yang Miao; Baeyens Jan (E3S Web of Conferences)
The climate crisis requires urgent actions to reduce the global temperature. Renewable energy and electro-chemicals are expected to play a growing role in sustainable power solutions moving forward. Hydrogen-based approaches are projected to emerge as the main long-term strategy. With declining expenses for solar panels and wind energy systems, building electrolyzers near renewable power sites has emerged as a viable hydrogen production method. A fossil-free approach for generating H2 would involve utilizing carbon-neutral raw materials. Preliminary studies examined this concept through methanol, ethanol and ammonia processing. Water decomposition via reversible oxidation-reduction cycles is considered a superior method under investigation. Renewable thermal or electrical input will be essential and is being studied, particularly through implementation of Concentrated Solar Tower systems. The investigation yielded test outcomes and engineering specifications, highlighting requirements for further advancements.